Neonatal Sleeve Gastrectomy for Multiple Gastric Perforations: A Case Report - Francisco Reyna-Sepulveda (EL-Med-Pub, 2016)
Neonatal gastric perforation (NGP) may be spontaneous, secondary to necrotizing enterocolitis (NEC), or due to distal obstruction. A 27-week old premature male newborn presented with pneumoperitoneum. A single perforation of stomach was found at surgery. Primary repair and gastrostomy were performed. On fifth postoperative day, pneumoperitoneum was again detected. At reoperation, multiple gastric perforations of the greater curvature were found. Sleeve gastrectomy was performed. The patient responded well to the treatment.